Exponential stability of uncertain switched systems with multiple non-differentiable time-varying delays - T. La-Inchua (2018)
In this paper, the design of switching rule for exponential stability of a class of uncertain switched systems with delays is studied. The systems to be considered are linear and the state delays are time-varying. Based on Lyapunov functional and average dwell time approach, condition on the derivative of time-delay functions are not need to design switching rule for the exponential stability of switched systems with time-varying delays. The delay-dependent stability conditions are presented in terms of LMIs which can be solved easily by various available algorithms. The effectiveness of the proposed method is demonstrated by a simulation example. © 2013 T. La-inchua and P. Niamsup.